PWE-198 Propofol assisted endoscopy on day-case endoscopy unit—"the experience". (28th May 2012) - Murugesan, S V; Davies, M; Haslam, N; Smart, H L; Sarkar, S
Abstract : Introduction: Patients intolerant of endoscopic procedure under conscious sedation subsequently have the procedure under a general anaesthetic. Provision of deep sedation (with propofol) has also been used in this setting. Aim: To assess the safety profile and patient satisfaction with deep sedation using propofol for endoscopic procedures in a dedicated deep sedation endoscopy list. Methods: Retrospective analysis of cases performed between June and December 2011. Cases were performed on a dedicated weekly "deep sedation" list supervised by a consultant anaesthetist in the endoscopy Unit. Anaesthetic records, case records and GI reporting tool (UNISOFT ® ) were interrogated for data. Satisfaction scores (score 1=unsatisfactory; 5=fully satisfied) were recorded for patients, anaesthetists and endoscopists post procedure. Results: 40 patients, 19 (47.5%) female with a median age of 53 years (range 18–80 years), underwent propofol assisted endoscopy. Mean ASA grade was 2 (range 1–3). 24 (60%) had unsatisfactory endoscopy previously under conscious sedation for phobia, anxiety, pain (colonoscopy) and stricture requiring dilatation. Procedures: 16 (40%) underwent radio frequency ablation of dysplastic lesion in Barrett's oesophagus (HALO ® ) and 14 (35%) underwent colonoscopy, with the remainder undergoing ERCP (n=3, 7.5%), gastroscopy (n=2, 5%), ampullectomy (n=2, 5%), small bowel enteroscopy (n=1, 2.5%) and endoscopic ultrasound (n=2, 5%). Mean waiting time was 8 weeks. All procedures were successfully completed with mean duration of 33 min per procedure (range 10–70 min). Mean propofol dose administered was 333 mg (range 41–1178 mg) and in addition fentanyl (mean dose 50 μg), midazolam (mean dose 1.5 mg), hyoscine hydrobromide (20 mg) and intravenous paracetamol (1 g) were administered as required. No reversal agents were required for any of the procedures. Adverse Events: Overall rate was 10% and minor. Transient hypoxia (SpO2 <90%) in two patients, relieved with jaw thrust, one patient required an airway device and persistent hypotension in two patients required vasopressors. All patients were discharged as day-cases. There were no 7-day readmissions or 30-day mortality. Median satisfaction scores for the procedure were high for patients (5), for anaesthetists (5) and for endoscopists (5). Conclusion: Anaesthetic led propofol assisted endoscopy is safe in a day-case endoscopy unit and is associated with high satisfaction scores for patient, anaesthetist and endoscopists. Competing interests: None declared.